2016
DOI: 10.1016/j.virol.2016.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Dengue virus NS1 enhances viral replication and pro-inflammatory cytokine production in human dendritic cells

Abstract: Dengue virus (DV) has become the most prevalent arthropod borne virus due to globalization and climate change. It targets dendritic cells during infection and leads to production of pro-inflammatory cytokines and chemokines. Several DV non-structural proteins (NS) modulate activation of human dendritic cells. We investigated the effect of DV NS1 on human monocyte- derived dendritic cells (mo-DCs) during dengue infection. NS1 is secreted into the serum of infected individuals where it interacts with various imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 60 publications
2
42
0
Order By: Relevance
“…The viral titer did not experience a significant increase in cells pre-incubated with 3.5 ug/mL or 7 ug/mL of NS1, perhaps due to a saturation of the system. This result suggests that exposure and internalization of NS1 by C6/36 cells before viral infection favors viral particles production, in agreement with previous results reported for liver and dendritic cells (Alcon-Le Poder et al, 2005; Alayli and Scholle, 2016).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The viral titer did not experience a significant increase in cells pre-incubated with 3.5 ug/mL or 7 ug/mL of NS1, perhaps due to a saturation of the system. This result suggests that exposure and internalization of NS1 by C6/36 cells before viral infection favors viral particles production, in agreement with previous results reported for liver and dendritic cells (Alcon-Le Poder et al, 2005; Alayli and Scholle, 2016).…”
Section: Resultssupporting
confidence: 93%
“…It is well established that DENV NS1 is internalized in human hepatic and dendritic cells, rendering the cells more susceptible to DENV infection (Alcon-LePoder et al, 2005; Alayli and Scholle, 2016); yet internalization of DENV NS1 in mosquito cells or of ZIKV NS1 in any cell type have not been reported. Thus, using Huh-7 liver cells in parallel, we evaluated if DENV and ZIKV NS1 were also internalized by C6/36 mosquito cells after 1 or 2 hours of incubation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the time of FDA approval for the particular study, the test was already in use in approximately 40 countries around the world [20]. The USNIH notes on https://www.clinicaltrials.gov that the study has been completed but official results are yet to be reported [21]. In Lima et al [22], two of the previously mentioned assays, the PanBio ELISA and the Platelia™ EIA, were compared against another immunoassay, the Dengue NS1 STRIP (Bio-Rad, Hercules, CA).…”
Section: Discussionmentioning
confidence: 99%